La mobilisation des acteurs locaux en réaction aux projets d’aménagement des fronts d’eau de Rabat : Émergence de nouveaux acteurs et évolution des répertoires de l’action collective - Hicham Mouloudi (L’Année du Maghreb)
On the model of multiple cities around the world, the agglomeration of Rabat-Salé is the setting for a proactive policy of waterfront development. The development project of the Bou Regreg valley is a prime example of this new urban ambition.For efficiency, a custom players system was set up for the realization of this project. However, the State remains much the leading player in the development and management of the city, at the expense of elected representatives, associations and ordinary citizens. The consequence of this unequal power relationship is the emergence of several development conflicts. These conflicts have led all who were affected by the development of the Bou Regreg valley to mobilize and put pressure on decision makers and to develop the range of their collective action. This forced the project manager to accept many compromised solutions.